Hidden Urban Biodiversity: A New Species of the Genus Scincella Mittleman, 1950 (Squamata: Scincidae) from Chengdu, Sichuan Province, Southwest China - Ru-Wan Jia; Zong-Yuan Gao; Di-Hao Wu; Guan-Qi Wang; Gang Liu; Min Liu; Ke Jiang; De-Chun Jiang; Jin-Long Ren; Jia-Tang Li (Animals)
The genus Scincella Mittleman, 1950, belonging to the family Scincidae, exhibits considerable morphological convergence, complicating species delimitation and resulting in underestimated diversity. Currently, 41 species are formally recognized in this genus, although this figure likely underestimates its true richness. In this study, a new species of the genus Scincella, Scincella chengduensis sp. nov., is described from urban and suburban areas of Chengdu, Sichuan Province, Southwest China. Morphological features and phylogenetic analyses confirmed that the new species is distinct from all previously recognized congeners. The new species can be clearly distinguished by a combination of the following unique characters: (1) slender, medium-sized body, snout-vent length 28.4–43.2 mm; (2) infralabials seven, rarely six; (3) supraciliaries six or seven; (4) tympanum deeply recessed without lobules, tympanum diameters equal to or exceeding palpebral disc diameters; (5) midbody scale-row counts 23; (6) dorsal scales smooth, slightly enlarged, paravertebral scale-row counts 57–60, ventral scale-row counts 42–44, gulars 21–22; (7) upper edge of lateral longitudinal stripes relatively straight, four rows of dorsal scales in middle; (8) enlarged, undivided lamellae beneath finger IV 8–9, enlarged, undivided lamellae beneath toe IV 10–12; (9) ventral surface densely covered with dark spots; (10) grayish-brown, irregular dorsal stripes 2–3, black dorsolateral stripes from posterior corner of eye to lateral side of tail. This discovery underscores the underestimated diversity of Scincella in China and highlights the importance of urban habitats as reservoirs of hidden biodiversity. A diagnostic key to the Scincella species of China is also provided.